Retention Challenges in Opioid Use Disorder Treatment: The Role of Comorbid Psychological Conditions - David C. Seaberg; Jamie McKinnon; Lyn Haselton; Patrick Palmieri; Jason Kolb; Suman Vellanki; Mary Moran; J. Chika Morah; Nicholas Jouriles (Western Journal of Emergency Medicine)
Introduction: Comorbid psychological conditions have an impact on opioid use disorder (OUD). We measured multiple psychological tests in OUD patients who entered an emergency department (ED)-based medication for opioid use disorder (MOUD) program to determine whether any test correlated with six-month retention in the MOUD treatment program. Methods: Patients with OUD who were enrolled in an ED-based MOUD program over a 12-month period were eligible to participate. We surveyed enrollees using nine validated tools to assess depression, anxiety, and traumatic stress within 24 hours of their ED presentation and then at one and six months. The primary outcome was program retention rates at one and six months. Secondary outcomes were levels of clinical symptoms, substance use, and quality of life. Results: Of 143 patients enrolled in the MOUD program, 64 (44.8%) participated during the 12-month study. The mean age was 33 years, with 65% male and 35% female. Baseline surveys indicated moderate symptom severity for depression and anxiety. The Post-Traumatic Stress Disorder Checklist (PCL-5) scores showed significant traumatic stress. Retention rates were 47% at one month and 25% at six months. General well-being improved from 40% at baseline to 56% at six months. Average income correlated (0.51) with six-month retention, suggesting that those with financial means were more likely to remain in treatment. The Life Events Checklist (LEC-5) correlated (0.41) with six-month retention. This indicates that the more trauma an individual experienced, the less likely the person would remain in treatment. Conclusion: Higher income and lower post-traumatic stress disorder scores had higher retention rates in a medication-based opioid use disorder program. Psychological surveys of patients entering a MOUD program may help predict treatment retention. There will likely be challenges in keeping patients with extensive trauma histories retained in treatment.